Determinants of Delays in Corporate Reorganizations - Brunassi Silva, Vinicius Augusto; Saito, Richard; Manoel, Paulo Martins; Calabrez Oreng, Mariana Aparecida (Review of Business Management, 2020)
Purpose – Firms and creditors may delay certain decisions in corporate reorganizations because of actions that require coordination. This paper investigates delays in voting on reorganization plans during claimholder general meetings in Brazil. Design/methodology/approach – Using a sample of 120 hand-collected reorganization plans, we present descriptive and regression (OLS, Poisson, negative binomial, and quantile) analyses to show the primary characteristics of delayed votes. Findings – Our results revealed that a high concentration of debt among the different classes of claimholders appeared to be related to fewer delays. Moreover, a higher number of banks and secured creditors with claims in the reorganization appeared to be positively correlated with delays. Finally, we argue that reorganization plans that require additional time to reach a vote are related to divestment proposals. Originality/value – There is still a lack of empirical results based on evaluations of multiple creditor characteristics and the reorganization proposals presented in firms’ reorganization plans. This is the first paper in Brazil to explore how conflicts of interest among different classes of creditors may relate to delays. Our paper contributes to the literature developed by Gilson (1990), Gilson et al. (1990), Brown et al. (1993), Franks and Tourus (1994), Helwege (1999), Ayotte and Morrison (2009), Ponticelli (2012), and Ivashina et al. (2015) regarding the characteristics of delaying reorganization plan votes during restructuring cases. We corroborate the results obtained by previous papers and provide an analysis of the role played by each class of claimholder in delaying plan votes for Brazilian firms